Exploring the Plasma Proteome Networks: Unravelling Insights into Ischemic Stroke Pathophysiology - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Ischemic Stroke (IS), a devastating cerebrovascular event, remains a leading cause of death and disability worldwide. It occurs when a blood clot blocks an artery supplying blood to the brain, leading to a sudden loss of blood flow and oxygen deprivation. T he resulting tissue death can cause a range of neurological impairments, impacting everything from movement and speech to cognitive function and emotional regulation.1-3 The severity of the stroke and the individual's long-term prognosis depend on various factors, including the location and size of the blockage, the duration of blood flow interruption and pre-existing health conditions.4,5 Despite significant advancements in stroke management, early and accurate diagnosis is crucial for maximizing treatment efficacy and minimizing long-term complications.6,7 Traditionally, stroke diagnosis relies heavily on clinical assessment tools like the National Institutes of Health Stroke Scale (NIHSS) and neuroimaging techniques such as Computed Tomography (CT) and Magnetic Resonance Imaging (MRI).6,7 However, these methods have limitations. Clinical assessment can be subjective and may be unreliable in patients with limited communication abilities.